Cooperation with Zimbabwe - Walraet, Anne (Afrika Focus, 1990)
Following last year’s decision by the Belgian Ministry of Development Cooperation to streamline all bilateral aid programmes to the countries of Southern Africa in order to take account of the new regional emphasis, it makes sense now to reflect on cooperation with Zimbabwe in the context of cooperation with the SADCC. The above decision was preceeded by the allocation of a regional budget of BEF 600 million for SADCC projects and is accompanied by the setting up in Harare of a field office serving as headquarters for the whole region (except Tanzania). All these innovations must be welcomed; they imply the recognition of the SADCC and are congruent with the recommendations of a joint study by the SADCC and the OECD Development Centre, dating back to 1987.